CONFLICT AND VIOLENCE WITHIN THE HIBUA LAMO COMMUNITY IN TOBELO NORTH HALMAHERA - Elsina Titaley; Abubakar Muhammad Nur (Universitas Padjadjaran, 2022)
The Hibua Lamo Community (ethnic Tobelo) is a community group that lives and integrates integration in the North Halmahera region and is characterized by the treatment of customs. In social life, they always lived in harmony and peace, since 1606, under the foundation of cultural values. In 1999-2001, Hibua Lamo community was faced by conflict and violence between brotherhood caused of religions that triggered them to kill each other. The purpose of this research is to describe and analyze the background of conflict in Hibua Lamo community. This qualitative research includes ethnographic research on the Hibua Lamo community. The results show that the conflict in the Hibua Lamo community was triggered by the conflicts among religious adherents in Ambon 1999. This article has its own distinctive characteristics that are different from other articles becuase the researcher is an aboriginal who saw for himself the conflicts that occurred in 1999 in North Halamahera and was confirmed by important important figures in the HL community. There are three factors that are escalators of conflict and violence within the Hibua Lamo community: (1) Fanaticism of each adherent of religion, (2) Fragment of noble values in Hibua Lamo culture, (3) exodus community groups as victims of violent conflict in Ambon, each carrying information according to the suffering they experience, leads to a sense of the devout by each adherent of religion (Islam and Christian) within Hibua Lamo community, North Halmahera. This study recommends that the Hibua Lamo concept can be considered to resolve conflicts.